The impact of sensory marketing on street food for the return of international visitors: Case study in Vietnam - Sinh Duc Hoang; Zuzana Tučková (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
This research was conducted to check the impact of factors related to sensory marketing on street food to the return of international visitors in Ho Chi Minh city (HCMC). The study applied the PLS-SEM model to estimate with five scales groups of factors related to sensory marketing (such as visual, tactile, auditory, olfactory, and flavorful factors). And using the surveyed and cleaned up data with reliable information of 250 international tourists in HCMC in 2020. The research results found that all factors in the proposed research model have a positive statistically significant effect on visitor satisfaction on street food. And then, street food satisfaction continues having a positive effect on the return to HCMC. The degree of influence of Sensory marketing factors on street food to Visitor satisfaction in descending order is as follows: (1) The smell of street food; (2) the sound of the food and drink shops, street vendors; (3) taste of street food; (4) sight of street food; (5) Tourist's touch to the equipment and street vendors. This paper contributes to provide more empirical evidence to fill the current research gaps regarding the impact of sensory marketing on revisit decisions in Vietnam. Moreover, this really usefull for HCMC tourism to build a marketing strategy, design marketing programs on cuisine suited to promote, attract more international tourists to return in the future.
Keywords: M31; Z32; 330; Sensory marketing; Visitor satisfaction; Revisit decisions; Return decision; International tourists; Street food; Ho Chi Minh City